Finite Element Analysis of Dynamic Meshing Characteristic of Skew Bevel Gear with Equivocal Modification - Xiaoping Ran; Liyao Gu; Jianfan Wang (Jixie chuandong)
On the basis of the principal of gear generating machining method，the gear flank mathematical model and gear tooth flank contact line equation of skew bevel gears with equivocal modification are derived，the contact finite element dynamic analysis model with seven teeth is built，the position of edge contact in a meshing period，as well as the variation curves of contact stress and bending stress under different loads are obtained. The variation rule of normal contact force and the contact ratio of skew bevel gears in stable meshing period are analyzed. The result shows that edge contact occurs when skew bevel gears enter and exit meshing process. The contact force curve in the entire meshing period is smooth，which is symmetrically distributed near the three-tooth meshing period and has a high contact ratio. The maximum bending stress occurs near the tooth root transition fillet of the large end of the driven gear and the small end of driving pinion.